2014
DOI: 10.1136/gutjnl-2014-307720
|View full text |Cite
|
Sign up to set email alerts
|

Iron fortification adversely affects the gut microbiome, increases pathogen abundance and induces intestinal inflammation in Kenyan infants

Abstract: NCT01111864.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
510
11
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(590 citation statements)
references
References 67 publications
21
510
11
8
Order By: Relevance
“…Thus, the Fe in the LNS improved Fe stores but may not have stimulated reticulocytosis, which might explain the lack of adverse effects on malaria morbidity. Our findings are different from the reports of the studies in Pakistan (6) , Kenya (7) , Pemba (8) , Zambia (10) and Cote d'Ivoire (35) . These studies reported increases in malariarelated hospitalizations and deaths, respiratory infections, diarrhoea and intestinal inflammation associated with Fe supplements or Fe-containing MNP provision in children.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the Fe in the LNS improved Fe stores but may not have stimulated reticulocytosis, which might explain the lack of adverse effects on malaria morbidity. Our findings are different from the reports of the studies in Pakistan (6) , Kenya (7) , Pemba (8) , Zambia (10) and Cote d'Ivoire (35) . These studies reported increases in malariarelated hospitalizations and deaths, respiratory infections, diarrhoea and intestinal inflammation associated with Fe supplements or Fe-containing MNP provision in children.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a recent study reported that mice fed a high-iron diet had lower abundances of Bifidobacteriaceae and Lactobacillaceae than mice fed a normal-iron or iron-deficient diet (38). In addition, the pathogenic bacteria Salmonella and Escherichia coli were increased in infants with iron fortification (39). Although the mechanisms remain unclear, these studies show imply that iron intake influences gut microbiota composition.…”
Section: Discussionmentioning
confidence: 86%
“…Carcinoma-enriched bacteria such as B. massiliensis, P. merdae, A. finegoldii and B. wadsworthia were less abundant in subjects consuming more vegetable or fruits, in contrast to the control- Serum levels of ferritin, a protein responsible for intracellular iron storage, negatively correlated with many of the carcinomaenriched MLGs (Fig. 6), highlighting iron as a key resource for the growth of a number of pathogenic bacteria 26 , which feed on iron from the host or dietary sources such as meat. Haemoglobin (Hb) displayed negative correlation with the carcinoma-enriched mlg-75, mlg-2985, mlg-88 and mlg-84.…”
Section: Resultsmentioning
confidence: 99%